Dirty Cities
XIII, 223 p.
Keywords: This volume uncovers the relations between globalization and dirty dealings in urban settings, focusing on some capital cities and on the relations between underground and overground dynamics all over the globe. It aims to provide a new take on the dark side of globalization.